HPTLC Fingerprinting and Antioxidant Potential Assessment of Methanolic Extract of Vitex negundo Leaves - Saboo, Shweta S.; Nimbalkar, Vaishanavi Bhimrao (Free Radicals and Antioxidants, 2025)
Background: Vitex negundo Linn. is a well- honored medicinal factory known for its different pharmacological properties, largely attributed to its rich phytochemical composition. Glycosidic composites, in particular, contribute significantly to its remedial eventuality, including antioxidant exertion. This study aimed to estimate the phytochemical ingredients and antioxidant exertion of the methanolic excerpt of Vitex negundo Linn. leaves, with emphasis on glycosidic enrichment using an optimized birth system. Materials and Methods: Methanolic birth of Vitex negundo leaves was performed, followed by primary phytochemical webbing. Quantitative estimation of total phenolic content (mg GAE/ g), total flavonoid content (mg shaft/ g), and total tannin content (mg TAE/ g) was carried out using standard spectrophotometric styles. Phytochemical profiling was conducted using Thin Subcaste Chromatography (TLC) and High-Performance Thin- Subcaste Chromatography (HPTLC). An advanced birth protocol involving mild acid hydrolysis, solvent phase partitioning, and chromatographic refinement was employed to widely enrich glycosidic fragments. Results: The excerpt showed the presence of flavonoids, phenolics, tannins, glycosides, alkaloids, and saponins, with considerable situations of antioxidant-related composites. TLC and HPTLC biographies verified distinct phytochemical patterns and effective glycoside enrichment. Conclusion: Vitex negundo leaves retain significant antioxidant eventuality, and the optimized system efficiently amended glycosidic composites of pharmacological significance.
Keywords: Antioxidant; High Performance Liquid Chromatography; Phenolic; Thin Layer; chromatography; Vitex negundo